Are the oxygen uptake and heart rate off-kinetics influenced by the intensity of prior exercise? - do Nascimento Salvador P.C. (2016)
© 2016 Elsevier B.V.The aim of this study was to investigate the effect of prior exercise on the heart rate (HR) and oxygen uptake (VO2) off-kinetics after a subsequent high-intensity running exercise. Thirteen male futsal players (age 22.8 ± 6.1 years) performed a series of high-intensity bouts without prior exercise (control), preceded by a prior same intensity continuous exercise (CE+CE) and a prior sprint exercise (SE+CE). The magnitude of excess post-exercise oxygen consumption (EPOCm - 4.25 ± 0.19 vs. 3.69 ± 0.20 L min-1 in CE+CE and 3.62 ± 0.18 L min-1 in control; p < 0.05) and the parasympathetic reactivation (HRR60s - 33 ± 3 vs. 37 ± 3 bpm in CE+CE and 42 ± 3 bpm in control; p < 0.05) in the SE+CE were higher and slower, compared with another two conditions. The EPOCτ (time to attain 63% of total response; 53 ± 2 s) and the heart rate time-course (HRτ - 86 ± 5 s) were significantly longer after the SE+CE condition than control transition (48 ± 2 s and 69 ± 5 s, respectively; p < 0.05). The SE+CE induce greater stress on the metabolic function, respiratory system and autonomic nervous system regulation during post-exercise recovery than CE, highlighting that the inclusion of sprint-based exercises can be an effective strategy to increase the total energy expenditure following an exercise session.